ChemInform Abstract: Pd‐Catalyzed Cross‐Coupling Study of Bi‐Functional 3‐Bromo‐4‐trifloxycoumarins with Triarylbismuth Reagents. Issue 44 (15th October 2015) - Rao, Maddali L. N.; Kumar, Abhijeet
Abstract An efficient method for the chemoselective synthesis of various mono‐, di‐, and triarylated coumarins is disclosed.